2016
DOI: 10.1177/1359105316642831
|View full text |Cite
|
Sign up to set email alerts
|

Continuous traumatic stress as a mental and physical health challenge: Case studies from South Africa

Abstract: This article discusses the condition of continuous traumatic stress as common on the African continent and in other international settings characterised by very high levels of ongoing violence and threat of community, political or war-related origin. Through consideration of three case studies from South Africa, contexts of continuous traumatic stress are described, and the mental health and physical health effects of living in such contexts are elaborated. Cautions are raised about attempting to transpose exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…[13] An important evolution of the thinking around trauma has come with the notion of continuous trauma, which attempts to define traumatic stress when there is a psychological impact that is real and ongoing, with current threat and danger. [14] This is a deviation from the more common understanding of PTSD that implicitly manages the effects of trauma in the past, with an acceptance that the threat is no longer current and real. Although some people who have experienced traumatic events in the past may currently reside in an objectively safe environment, this is not the case in contexts of protracted civil conflict, mass displacement, enduring IPV or high levels of community violence.…”
Section: The Golden Thread: a Focus On Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] An important evolution of the thinking around trauma has come with the notion of continuous trauma, which attempts to define traumatic stress when there is a psychological impact that is real and ongoing, with current threat and danger. [14] This is a deviation from the more common understanding of PTSD that implicitly manages the effects of trauma in the past, with an acceptance that the threat is no longer current and real. Although some people who have experienced traumatic events in the past may currently reside in an objectively safe environment, this is not the case in contexts of protracted civil conflict, mass displacement, enduring IPV or high levels of community violence.…”
Section: The Golden Thread: a Focus On Mental Healthmentioning
confidence: 99%
“…Continuous traumatic stress therefore offers a particularly valuable local clinical dimension, with concomitant treatment recognising the ongoing nature of the traumatic experience. [14] It is important to note that IPV has mental health consequences for both victims and their communities. A recent nationally representative study in SA found that increased depressive symptoms among women are associated with an increase in the perceived frequency of neighbourhood domestic violence, highlighting the communitylevel mental health effects of such violence.…”
Section: The Golden Thread: a Focus On Mental Healthmentioning
confidence: 99%
“…Stevens et al [24] trace the history of the development of PTSD, illustrating how historically it has dominated the research on trauma, reflecting the experience of high-income countries, to the exclusion of other forms of trauma which may be part of life for people in low-income countries, countries which are in the midst of civil conflict, or societies in which there is ongoing poverty, community violence, scarcity of resources, or political oppression [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Case studies are particularly helpful in giving rich information about issues which may be used for future research and for setting agendas for future, larger-scale studies [12,13]. For the current research, the case-study approach outlined by Kaminer et al [14] in their work on continuous traumatic stress in South Africa was followed. A key feature of their approach to case studies is the careful attention not only to the personal context of health issues but also to the political context.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation